Beyond “Industry 4.0": B2B factory networks as an alternative path towards the digital transformation of manufacturing and work - Florian BUTOLLO; Lea SCHNEIDEMESSER (International Labour Review, 2021)
This article uses theoretical and empirical evidence of variations in digitalized manufacturing to revisit Piore and Sabel's 1984 work on flexible specialization and to criticize the inherent one-sidedness of the Industry 4.0 discourse. This is juxtaposed with empirical findings on platform-mediated business-to-business factory networks, in which flexibility is facilitated by the digital interconnection of a far-flung network of small-scale manufacturers rather than by sophisticated production technology. The effects on work are equivocal; they entail the potential for a craft-like and skill-intensive paradigm of small-scale manufacturing that can upgrade work, but also for a race to the bottom in price-sensitive industries.
Keywords: 330; Industry 4.0; flexible specialization; digitalization; platform; global value chains; upgrading; Alibaba